Studies on the drying of oyster mushrooms (Pleurotus sajor-caju) and its utilization in mushroom-incorporated cookies - Ritika,; Kumar, Krishan; Sanyukta,; Kaur, Manjot; Kaur, Navjot; Samyor, Duyi; Ahmed, Naseer; Sheikh, Aaqib (Journal of Postharvest Technology, 2022)
The present investigation was carried out to study the drying of oyster mushrooms by involving two  methods, namely hot-air oven drying and vacuum drying, after different pre-treatments. There was  a decrease in browning of mushrooms dried after blanching and steeping in anti-browning agents  such as citric acid (0.5%) and ascorbic acid (0.5%). The browning was observed to be lowest in  vacuum-dried mushrooms compared to hot-air oven-dried mushrooms. Therefore, the mushrooms  dried by vacuum drying techniques, pre-treated with citric acid (0.5%) and ascorbic acid (0.5%)  solutions after blanching, were utilized for the preparation of mushroom powder for incorporation  in cookies. The cookies were prepared by incorporating mushroom powder at 5%, 10%, and 15%  by replacing wheat flour and were subjected to organoleptic evaluation by a semi-trained panel.  The cookies were moderately acceptable, having an organoleptic score of more than 7.0 as per a  9-point hedonic rating scale. However, the cookies containing a higher level of mushroom powder  (15%) scored slightly lower (having an overall score of less than 7) compared to other formulations.  These products can provide significant support against protein-energy malnutrition (PEM), obesity,  cardiovascular diseases, diabetes, and other lifestyle disorders that have a wide prevalence in  different sections of society.
Keywords: Cookies; hot air oven drying; organoleptic evaluation; oyster mushroom; vacuum oven drying